2020
DOI: 10.1186/s43094-020-00104-3
|View full text |Cite
|
Sign up to set email alerts
|

The comparison between curcumin and propolis against sepsis-induced oxidative stress, inflammation, and apoptosis in kidney of adult male rat

Abstract: Background Propolis is a honeybee product displaying an anti-inflammatory, antimicrobial, and antioxidant effect on several tested animal models. Curcumin a polyphenol extracted from turmeric that gained interest as a potentially safe and inexpensive treatment for kidney diseases. The present study aimed to compare the protective effects of curcumin and propolis on endotoxemia-induced renal dysfunction. Results Sepsis induction caused a marked decline in renal GSH, GPx, and GR, as well as antioxidant enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Forms (1,2,3,4) show a significant significance of (p≤0.05) in the activity of antioxidants in the tiles with the water extract and the alcohol for the propolis E.E.P when compared to the positive group and this result is compatible with [39], [40] as well as the study of [17] that referred to the role of alcoholic extracts of propolis in the events of a significant increase in the levels of antioxidants such as the SOD and the GPX. The study of [41] and [42] also agreed with the results of our study, which indicated the role of aqueous extract in preventing the damage and toxic effects of oxidative stress by increasing the capacity of antioxidants such as catalase and superoxide dismutase.…”
Section: Effect Of Aqueous and Alcoholic Extracts Of Propolis On Anti...supporting
confidence: 63%
“…Forms (1,2,3,4) show a significant significance of (p≤0.05) in the activity of antioxidants in the tiles with the water extract and the alcohol for the propolis E.E.P when compared to the positive group and this result is compatible with [39], [40] as well as the study of [17] that referred to the role of alcoholic extracts of propolis in the events of a significant increase in the levels of antioxidants such as the SOD and the GPX. The study of [41] and [42] also agreed with the results of our study, which indicated the role of aqueous extract in preventing the damage and toxic effects of oxidative stress by increasing the capacity of antioxidants such as catalase and superoxide dismutase.…”
Section: Effect Of Aqueous and Alcoholic Extracts Of Propolis On Anti...supporting
confidence: 63%
“…It displays an extensive range of biological activities, going from antioxidant, immunostimulant, antimicrobial, anti-inflammatory, and antiviral effects to anticancer activity [36,38,39] to tissue regenerating and healing in ulcers [38,40]. According to Abd-Elrazek and collaborators (2020), PRP can inhibit systemic inflammation, as well as decrease the oxidative stress by protecting the membranes and eliminating free radicals, evidencing its anti-inflammatory and antioxidant activities [41]. This drug is frequently processed as ethanolic extract (PE), which can be used as a final or intermediary dosage form [24,38,42].…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have also confirmed the hepatoprotective capacity of propolis against hepatotoxic compounds through its anti-inflammatory activities by down-regulating and/or inhibiting the expression of NF-κB, COX-2, transforming growth factor β (TGF-β), Bcl-2, and IL-6 [ 120 , 121 , 125 , 129 , 131 ]. Similar protective mechanisms and anti-inflammatory activities of propolis were also observed in the retina, skin, pancreas, spleen, kidneys, ovary, and heart [ 100 , 102 , 104 , 108 , 110 , 112 , 118 , 120 , 128 ].…”
Section: Resultsmentioning
confidence: 53%